2019
DOI: 10.1080/02670836.2019.1655862
|View full text |Cite
|
Sign up to set email alerts
|

Ferrite recrystallisation and intercritical annealing of cold-rolled low alloy medium carbon steel

Abstract: Static recrystallisation of cold-rolled AISI 4130 medium carbon steel in the ferritic regime and its response to intercritical annealing treatment are studied. A fine and recrystallised microstructure with improved mechanical properties is obtained via subcritical annealing of cold-rolled sheet, where the subsequent intercritical annealing results in the enhancement of tensile strength via the formation of dual-phase microstructure. Intercritical annealing of the cold-rolled sheet is characterised by an initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 60 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…Grain growth, essentially a grain boundary migration process, requires atomic diffusion, which accelerates with higher deformation temperatures, increasing the boundary migration rates, thus increasing the static recrystallization volume fraction. Related research [ 26 , 27 ] utilized multivariate nonlinear regression analysis to determine the coefficients and establish a model describing the static and dynamic recrystallization of steel microstructures. The study examined the influence of the initial grain size, deformation temperature, strain, and strain rate on the austenite recrystallization volume fraction and grain size.…”
Section: Discussionmentioning
confidence: 99%
“…Grain growth, essentially a grain boundary migration process, requires atomic diffusion, which accelerates with higher deformation temperatures, increasing the boundary migration rates, thus increasing the static recrystallization volume fraction. Related research [ 26 , 27 ] utilized multivariate nonlinear regression analysis to determine the coefficients and establish a model describing the static and dynamic recrystallization of steel microstructures. The study examined the influence of the initial grain size, deformation temperature, strain, and strain rate on the austenite recrystallization volume fraction and grain size.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the lower critical temperature Ac 1 of 727°C and the upper critical temperature Ac 3 of 805°C were determined based on dilatometry as reported in Refs. [21,22]. The as-quenched steel was tempered for holding times up to 4 h at subcritical temperatures of 550°C, 600°C, 640°C, and 700°C.…”
Section: Methodsmentioning
confidence: 99%
“…Applying a cold working and tempering on the initial steel was an effective way for improving the microstructure and mechanical properties of resultant DP steel [75][76][77]. As an example, Mazaheri et al [44] found that applying one step tempering to a cold-rolled ferriticpearlitic steel sheet prior to intercritical annealing resulted in DP steel, which showed increased yield and tensile strengths, but decreased uniform and total elongations.…”
Section: Common Plastic Deformation Techniquesmentioning
confidence: 99%